Lexical inferencing in a first and second language : cross-linguistic dimensions - Wesche, Marjorie Bingham, 1941- (Second language acquisition (Clevedon, England), 2009)
Lexical inferencing is a central process in both reading comprehension and word learning through reading. This title presents a comprehensive research review on second language lexical inferencing and a fresh study of first and second language lexical inferencing by speakers of Persian, French and English.